PP45 The Cost-Of-Illness Of Diabetic Macular Edema In Italy. (23rd December 2022) - Basile, Michele; Calabrò, Giovanna Elisa; Bandello, Francesco; Varano, Monica; Castronovo, Giuseppe; Amore, Filippo; Melchiorre, Tiziano; Cicchetti, Americo
Abstract : Introduction: Diabetic Macular Edema (DME) is an important complication of Diabetic Retinopathy (DR). Intravitreal steroids in slow-release systems represent a safe and effective therapeutic option for the management of DME, capable of improving patients' quality of life by reducing the number of injections thus increasing the therapeutic adherence and the effectiveness of the treatment. This study aims to determine the economic impact of DME and the consequences, in terms of both expenditure and organizational impact, associated with a greater use of the intravitreal dexamethasone implant. Methods: The analysis entailed the comparison between two scenarios: a first scenario based on the current use of therapeutic alternatives available in the Italian healthcare setting (as is) and an alternative scenario based on the assumption of an increased use of intravitreal dexamethasone implant (to be). The results of the analysis are expressed in terms of resource absorption associated with the two scenarios as well as in terms of the cost differential given by their comparison. Results: Despite an increase in expenditure in terms of acquisition costs of pharmacological alternatives (EUR 898, 362) and interventions provided (EUR 22, 093, 160), the greater use of prolonged-release dexamethasone allows for significant savings in terms of healthcare professionals' time, follow-up and productivity losses incurred by patient/caregiver. These reductions in healthcare costs resulted in a saving of EUR 1, 987, 678 over a 5-year period. Such a reduction would allow, considering a total annual management cost of EUR 6, 115 for the intravitreal dexamethasone, to treat 325 more patients at the same cost of the as is scenario based on the current rate of use of dexamethasone. Conclusions: In a context characterized by the need to increase the allocative efficiency of economic resources, the recourse to therapeutic alternatives, such as prolonged release dexamethasone, allowing the reduction of costs for the management of a given pathology is crucial to generate more value for patients and the entire society.